2018
DOI: 10.1152/ajpendo.00015.2018
|View full text |Cite
|
Sign up to set email alerts
|

Saturated fatty acid combined with lipopolysaccharide stimulates a strong inflammatory response in hepatocytes in vivo and in vitro

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease and consumption of high-fat diet (HFD) is a risk factor for NAFLD. The HFD not only increases intake of saturated fatty acid (SFA), but also induces metabolic endotoxemia, a HFD-associated increase in circulating lipopolysaccharide (LPS). Although it is known that SFA or LPS promotes hepatic inflammation, a hallmark of NAFLD, it remains unclear how SFA in combination with LPS stimulates host inflammatory response in hepatocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 57 publications
(77 reference statements)
6
24
0
Order By: Relevance
“…However, extracellular flux analysis in macrophages was not performed here due to well-known LPS-enhanced glycolysis ( 76 ). Our data support that saturated fatty acids, which are absorbed through portal vein ( 77 ), enhances LPS activity in hepatocytes and macrophages ( 53 , 54 ) and induced cytokine production ( 78 ). This suggests the inflammatory aggravating property of dietary saturated fatty acids on LPS + BG in sepsis with obesity.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, extracellular flux analysis in macrophages was not performed here due to well-known LPS-enhanced glycolysis ( 76 ). Our data support that saturated fatty acids, which are absorbed through portal vein ( 77 ), enhances LPS activity in hepatocytes and macrophages ( 53 , 54 ) and induced cytokine production ( 78 ). This suggests the inflammatory aggravating property of dietary saturated fatty acids on LPS + BG in sepsis with obesity.…”
Section: Discussionsupporting
confidence: 77%
“…Despite this limitation, LPS + BG altered cytokine responses and cell energy metabolism in hepatocytes enhanced by saturated fatty acid. This supports HFD-induced metabolic pro-inflammation ( 53 , 54 , 74 ). Saturated fatty acid alone did not alter cell energy metabolism of hepatocytes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Though the above findings corroborate the impact of total fat content on liver inflammation, multiple complex inflammatory mechanisms remain at play and SFAs still pose a significant threat to hepatocyte homeostasis. Of note, Li et al investigated the hepatic inflammatory response of SFA in combination with LPS in male low-density lipoprotein receptor deficient (LDLR -/- ) mice and in vitro in a mechanistic approach to elucidate the synergistic effects of LPS and SFA [141]. Mice were fed an HFD with high or low PA content (HP-HFD and LP-HFD) for 20 weeks where half were subsequently injected with LPS during the last 12 weeks of the dietary intervention.…”
Section: Lps Inflammation and Dietary Lipidsmentioning
confidence: 99%
“…Results showed that the HP-HFD in combination with LPS enhanced F4/80 expression more than the HP-HFD or LPS alone in liver tissue. Likewise, IL-6 protein expression in hepatocytes and mononuclear cells increased the most with the HP-HFD and LPS than either alone as determined by immunohistochemistry; the combination of the LP-HFD and LPS did not increase IL-6 protein expression to the same degree and LPS alone had no effect [141]. In hepatocytes in vitro , LPS stimulated both IL-6 secretion and gene expression while PA alone had no effect.…”
Section: Lps Inflammation and Dietary Lipidsmentioning
confidence: 99%